Regeneration of Raja (Musa AAB Group) and Kepok (Musa ABB Group) bananas on various stages of in vitro culture - Nazihah, Shafira Puti; Rahayu, Megayani Sri; Armini Wiendi, Ni Made (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Banana group can be divided into two groups based on their method of its utilization. Banana group that can be eaten immediately after ripening is called "dessert banana", e.g., Raja, while the group that needs particular processing before consumption is called "plantain banana", e.g., Kepok. This study aimed to compare the growth of Raja banana with Kepok plantain through experiments at three stages of the in vitro culture media: the shoot initiation, shoot multiplication, and plantlet acclimatization, also to compare the growth of Raja bananas with Kepok plantains in response to cytokinins BAP and TDZ at shoot multiplication stage. Planting material was in the form of rhizomes that was prepared with the same size. The experiment was performed using a completely randomized design. Results showed that Kepok plantain could adapt faster to the media condition than Raja banana; the phenomenon was evident in the growing speed of Kepok during shoot initiation stage. The proportion of the B genome did not show a direct effect on shoot induction at the multiplication stage or enlargement and organ formation at the acclimatization stage. Shoot induction at the multiplication stage depended more on the composition of the media used. The combination of BAP 3 mg L-1 and TDZ 0.01 mg L-1 in MS media produced the best shoot induction rate, and TDZ 0.01 mg L-1 in MS media had the highest shoot elongation rate. Keywords: banana, BAP, genome, PGR, plantain, TDZ